HAMBATAN PARTISIPASI PETANI DALAM PENGEMBANGAN PADI ORGANIK DI KABUPATEN TASIKMALAYA - Mimin Aminah (Graduate School Bogor Agricultural University (SPs IPB), 2018)
Farmers' participation in the group is required to overcome the various obstacles of deficiency, commitment development, motivation encouragement, credibility establishment, and bargaining power strengthening. Results of processing using ISM indicated that the end target of the completion of participation obstacles is to resolve the bottleneck of